Representações sociais de homens sobre o exame preventivo do câncer de próstata - Olivieri, Marcela (2016)
Prostate cancer is the 6th most common type of cancer worldwide and the 2nd most prevalent in Brazil so precocious diagnosis in the early stages can reduce its morbidity and mortality rates. Gender conceptions represent an important contribution to understanding of the cultural barriers of men to carry out the preventive examination, especially the digital rectal examination. Therefore, to reveal what men think and feel about the preventive examination will be able to subsidize new educative approaches regarding the adoption of preventive examinations. This study had as the main goal to investigate the social representations of men who search the Bus of the Men (Ônibus do Homem) about prostate cancer prevention. Twelve men were interviewed during the medical consultation carried by the Bus of the Men that goes through different neighborhoods of Sorocaba city in the state of São Paulo. The data collection was made by recorded oral interview gathering opinions, feelings and reasons for the adoption or refusal of the prostate cancer preventive examinations by the interviewees, as well as adoption and sociodemographic question form offered by the mobile unit. The interviews were organized according to a collective subject speech, and for the data analysis and interpretation a content analysis was used, subject area analysis mode. The results have shown that 41,7% of the participants go through preventive examinations regularly. The most quoted barrier to the digital rectal examinations were sexism, embarrassment and prejudice. The most quoted reasons to adopt the examination were the importance of prevention and maintenance as well as media influence. In order to have more men adopting the prevention the following was suggested: prostate cancer counseling to the resistant, dissemination of information about prevention and the silent evolution of cancer, demystification and recruiting